1980
DOI: 10.2214/ajr.135.5.945
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal artery branches: percutaneous transluminal angioplasty

Abstract: NY 1 0467. Address reprint requests to S. Sprayregen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The major factor accounting for the differences in the results of our study and the better results pre- viously reported by us and by other authors appears to be patient selection. 6,7,27,28 Our early enthusiasm for these less-invasive procedures in carefully selected patients prompted us to expand the indications to include patients with longer occlusions, previously failed bypass grafts, or diffusely diseased arteries. Our hope was that these expanded indications for PTA would prove to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…The major factor accounting for the differences in the results of our study and the better results pre- viously reported by us and by other authors appears to be patient selection. 6,7,27,28 Our early enthusiasm for these less-invasive procedures in carefully selected patients prompted us to expand the indications to include patients with longer occlusions, previously failed bypass grafts, or diffusely diseased arteries. Our hope was that these expanded indications for PTA would prove to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…In the direct surgery of the aortic bifurcation, 25% of patients develop subsequent lesions in the inflow and 75% in the outflow tract [40]. Patency rates vary from 82% after 5 years to 72% after 10 years [29,32,41]. In extra-anatomical bypass, patency is 75% after 3 years with a limb salvage rate of 90% [28,42].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Dilatation (Dotter's technique) is a relatively recent technique and, therefore, results are difficult to evaluate. It appears more encouraging for iliac stenosis [41,58,59]; the patency rate at 5 years is at least 50% of the initial patency rate (77-92%). In lesions of the femoral artery, the early rethrombosis rate seems high and the patency rate after 5 years is lower (11.5%) [41].…”
Section: Surgical Treatmentmentioning
confidence: 99%